News with an attitude ideological perspectives in the historical press - Claridge, Claudia 1965- (John Benjamins Publishing Company, 2025)
This volume extends research on ideology in the news into the historical sphere, spanning discourse from the mid-seventeenth to the early twentieth century.
Description based on publisher supplied metadata and other sources
Keywords: Geschichte 1640-1926; Berichterstattung; Ideologie; Englisch; Presse; Aufsatzsammlung